Differential Requirements for Toll‐Like Receptor Signalling for Induction of Chemokine Expression by Herpes Simplex Virus and Sendai Virus - Melchjorsen, J. (Scand J Immunol, 2008)
Toll‐like receptors (TLRs) are pattern recognition receptors of the innate immune system, which recognize molecular structures on pathogens or cellular stress‐associated molecules. TLR–ligand interactions trigger activation of inflammatory signal transduction and expression of genes involved in host defense. In this study, we have examined the requirement for different TLR adaptor molecules in virus‐induced chemokine expression and are currently trying to identify the TLR involved. We have found that both a herpesvirus [herpes simplex virus (HSV)] and a paramyxovirus (Sendai virus) require a functional genome to induce expression or proinflammatory chemokines in human and murine monocytic cell lines. For both viruses, this is independent of the TLR adaptor molecules TRIF and Mal. However, overexpression of the Vaccinia virus‐encoded inhibitor of TLR‐signalling A52R or dominant‐negative MyD88 totally inhibited HSV‐induced RANTES expression but only partially prevented Sendai virus from inducing this chemokine. This suggests that HSV‐induced RANTES expression occurs via a TLR pathways, whereas Sendai virus utilizes both TLR‐dependent and ‐independent pathways to stimulate expression of RANTES. We are currently trying to identify the TLRs involved. Data from these studies will also be presented at the meeting.